Ultrastructural and biochemical aspects of matrix vesicle-mediated mineralization. Issue 2 (May 2017) - Hasegawa, Tomoka; Yamamoto, Tomomaya; Tsuchiya, Erika; Hongo, Hiromi; Tsuboi, Kanako; Kudo, Ai; Abe, Miki; Yoshida, Taiji; Nagai, Tomoya; Khadiza, Naznin; Yokoyama, Ayako; Oda, Kimimitsu; et al.
Summary: Matrix vesicle-mediated mineralization is an orchestrated sequence of ultrastructural and biochemical events that lead to crystal nucleation and growth. The influx of phosphate ions into the matrix vesicle is mediated by several proteins such as TNAP, ENPP1, Pit1, annexin and so forth. The catalytic activity of ENPP1 generates pyrophosphate (PPi) using extracellular ATPs as a substrate, and the resultant PPi prevents crystal overgrowth. However, TNAP hydrolyzes PPi into phosphate ion monomers, which are then transported into the matrix vesicle through Pit1. Accumulation of Ca 2+ and PO4 3− inside matrix vesicles then induces crystalline nucleation, with calcium phosphate crystals budding off radially, puncturing the matrix vesicle's membrane and finally growing out of it to form mineralized nodules.